Equal education (e2): easy-to-use application software to provide awareness on educational rights of children with disabilities in Malaysia - Othman, Muhammad Fikri; Rahmat, Nur Ezan; Abdul Aziz, Norazlina; Saripan, Hartini (Universiti Teknologi MARA, Kedah, 2023)
Education is important to everyone, especially children with disabilities. It plays an essential role in their life because education will ensure children with disabilities have a bright future, enable them to make decisions and allow them to participate fully in society. In Malaysia, even though the government provides educational rights for all citizens, the educational rights of children with disabilities are not fully protected. They are not given equal educational rights as other normal children to access education since there are some requirements imposed by the Ministry of Education and schools’ administrators. Besides, there are gaps in the current laws and regulations relating to the educational rights of children with disabilities in Malaysia, such as scattered laws, too general, and loopholes. Not to mention, society's negative perceptions towards children with disabilities alsoprevent them from enjoying their educational rights. Hence, children with disabilities in Malaysia cannot access education equally as other normal children. This application is developed to provide understanding to Malaysians on the educational rights of children with disabilities and to enhance their knowledge and awareness of laws and regulations relating to the educational rights of children with disabilities. Besides, this application is developed to provide a platform for the parent of childrenwith disabilities and members of society to exchange their views and thoughts regarding the special education system in Malaysia to enable children with disabilities to access equal educational rights as other normal children. The Equal Education (e2) application is easy to use, user-friendly, informative, efficient, and suitable to be used by all Malaysians.